Opportunities for human factors in machine learning - Baweja, Jessica A.; Fallon, Corey K.; Jefferson, Brett A. (Frontiers in Artificial Intelligence, 2023)
The field of machine learning and its subfield of deep learning have grown rapidly in recent years. With the speed of advancement, it is nearly impossible for data scientists to maintain expert knowledge of cutting-edge techniques. This study applies human factors methods to the field of machine learning to address these difficulties. Using semi-structured interviews with data scientists at a National Laboratory, we sought to understand the process used when working with machine learning models, the challenges encountered, and the ways that human factors might contribute to addressing those challenges. Results of the interviews were analyzed to create a generalization of the process of working with machine learning models. Issues encountered during each process step are described. Finally, recommendations and areas for collaboration between data scientists and human factors experts are provided, with the goal of creating better tools, knowledge, and guidance for machine learning scientists.